Validação de métodos nociceptivos elétrico, mecânico e térmico para avaliação de dor de equinos tratados com metadona associada à detomidinaou acepromazina - Lopes, Carlize [UNESP] (2014)
Recognition of pain is fundamental for the development of effective analgesic strategies, therefore, it is essential to develop valid and reliable instruments for assessment of pain. A valid instrument to recognize the pain should produce sensitive scores, which should be modified after the administration of analgesics and should not result in tissue damage, should be easy to apply, with a clear cut-off and present validity and reproducibility. This study aimed to compare the electrical, mechanical and thermal nociceptive stimuli and investigate their feasibility, repeatability, sensitivity and specificity in eight horses. In the second part of the study, the antinociceptive effects of intravenous administration of methadone combined with detomidine or acepromazine were evaluated in the same animals. The mechanical (M) and thermal in the limb (TL) stimuli were measured at the left and right metacarpus regions, respectively. The electrical stimulus (E) was measured at the left coronary band and thorax thermal stimulus (TT) in the thorax, caudal to the withers. In part 1 of the study, three real and one sham stimuli were randomly applied, for each of the four tests, giving a total of 32 stimulations/animal in each phase, repeated six months later. In the part 2 of the study, the horses were treated with saline (C), methadone (0,2 mg/kg) combined with detomidine (10 μg/kg) - MD or acepromazine (0,05 mg/kg), with a minimum of one week interval. Thresholds were measured before and at 15, 30, 45, 60, 75, 90, 105, 120 and 150 minutes after treatment. The agreement between observers measured by kappa coefficient was 90% for both phases grouped and 92% and 88% in phases 1 and 2, respectively. The M stimulus showed 100% agreement between observers, followed by TL (97%), E (84%) and TT (75%). Sensitivity and specificity were 89% and 92%, respectively. The Wilcoxon rank sum test and Wilcoxon signed rank test were used to compare differences ...